Perlindungan Hukum Terhadap Pemegang Polis Asuransi Jiwa - Agus Wasita (Business Economic, Communication, and Social Sciences (BECOSS) Journal, 2020)
Most of family in Indonesia do not have insurance to reserve enough fund that will provide financial stability to protect themself and their families . As a consequence, in the event of accident, family will go bankrupt because they take short cut sells all asset to overcome accident that happened. Base survey of some insurance companies, as high as 86 percents of our society are not yet have protected insurance because of misperception, l a large part of people not feel require insurance . Despite that, lack of understanding makes society have in mind that insurance as burden and viewed as expensive product that bring less benefit for them. Other Constraint is lack of information for insurance client in course of claim to get its rights . insurance claim process frequently become animus process between insurance client and insurance company even sometimes their dispute possibility continues become lawsuit which is wasting time and energy for both of them . Lack of understanding to insurance law makes society sometimes use the wrong ways to solve their insurance lawsuit. This research intention to returns the society perception to the correct ways.This research is part of the legal research literature by examining the library materials or the so-called normative legal research.The results showed that the country has made political efforts to protect the legal right of citizens with regard to insurance, but indeed such cases other law enforcement efforts is still a chore government never resolved.